2003
DOI: 10.1002/ajh.10369
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune cytopenia does not predict poor prognosis in chronic lymphocytic leukemia/small lymphocytic lymphoma†

Abstract: Chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) is characterized by an acquired immune defect that can cause autoimmune complications, including anemia and thrombocytopenia. We conducted an observational study of the epidemiology, clinical presentation and significance of autoimmune complications of CLL/SLL in 132 patients from a large population (>45,000 veterans), in which at least 90% of patients with CLL/SLL have been previously identified. Over a period of 12.5 years, 12 patients (9.1%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 24 publications
4
90
1
3
Order By: Relevance
“…Various studies conducted in United State, Israel, Spain, England and Rome have reported a frequency of positive DAT in 4.5%, 7%, 4.3%, 7.7% and 3.7% of CLL patients respectively (Kyasa et al, 2003;Lischner et al, l988;Moreno et al, 2010;Hamblin et al, 1986;Mauro et al, 2000). However the prevalence of DAT positivity in our patients appears to be higher than these studies conducted in western world.…”
Section: Direct Coombs Test Positivity In B-chronic Lymphoid Leukemiamentioning
confidence: 98%
“…Various studies conducted in United State, Israel, Spain, England and Rome have reported a frequency of positive DAT in 4.5%, 7%, 4.3%, 7.7% and 3.7% of CLL patients respectively (Kyasa et al, 2003;Lischner et al, l988;Moreno et al, 2010;Hamblin et al, 1986;Mauro et al, 2000). However the prevalence of DAT positivity in our patients appears to be higher than these studies conducted in western world.…”
Section: Direct Coombs Test Positivity In B-chronic Lymphoid Leukemiamentioning
confidence: 98%
“…Among the hematologic autoimmune disorders, AIHA is more common than ITP while in CLL, AIHA was 3.3 times more common than ITP (8)(9)(10)(11). Both are less frequent in non-CLL-NHL and AIHA was only approximately twice as frequent as ITP (AIHA 1.57%, ITP 0.76%).…”
Section: -31449mentioning
confidence: 98%
“…The frequency of ITP in chronic lymphocytic leukemia (CLL) and NHL has been determined in several studies . [8][9][10][11][12][13][14][15] We analyzed data of individual non-CLL NHL patients with ITP from published case reports and original series of our institute with regard to the temporal relationship between ITP and lymphoma, the frequency in NHL subtypes, laboratory data and treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, progressive versus indolent forms of the disease are not identified. In addition, the mechanisms accounting for cytopenias are not taken into consideration, yet there is some indication that patients with cytopenias of immune origin may have a better outcome than those in whom the cytopenia is caused by a massive infiltration of the bone marrow by neoplastic cells (5,6). In addition, clinical stages are not good predictors of response to therapy.…”
Section: Prognosis Of Patients With Cllmentioning
confidence: 99%